Eating what its other - rhetorics of eating: a reading of jacques derrida’s unpublished seminar manger l’autre (1989 – 1990) - Campos Salvaterra, Valeria (Faculdade de Filosofia e Ciências, 2021)
In the unpublished seminars given in the United States and France between 1989 – 1991, Manger l'autre: Politiques de l'Amitié and Rhétoriques du Cannibalisme, J. Derrida analyzes the rhetorical function that philosophical texts of the Western tradition give to the act of eating. As an act of incorporation of the alien and a gesture of trespassing the border between the exterior and the interior, eating has been used as a metaphor for the processes of understanding and idealization, as well as for the general dynamics of the relationship with other. Nevertheless, this tropic function of food reaches the very logic of philosophical discourse, as being also rhetorical. We analyze these functions by showing that they are structural to philosophy in general and special topics of Derrida's work in all his texts.